2023
DOI: 10.1007/s12035-023-03314-x
|View full text |Cite
|
Sign up to set email alerts
|

Selective Disruption of Perineuronal Nets in Mice Lacking Crtl1 is Sufficient to Make Fear Memories Susceptible to Erasure

Abstract: The ability to store, retrieve, and extinguish memories of adverse experiences is an essential skill for animals’ survival. The cellular and molecular factors that underlie such processes are only partially known. Using chondroitinase ABC treatment targeting chondroitin sulfate proteoglycans (CSPGs), previous studies showed that the maturation of the extracellular matrix makes fear memory resistant to deletion. Mice lacking the cartilage link protein Crtl1 (Crtl1-KO mice) display normal CSPG levels but impaire… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…After the threat of the rubber paw, we observed pupil dilation that can also be observed when only the threat is applied without prior exposition to the prosthesis and tactile stimulations (Figure S1). Pupil dilation has been shown to correlate with different arousal states (Reimer et al, 2014; Turner et al, 2023), attention (Abdolrahmani et al, 2021), as well as the processing of startling stimuli (Leuchs et al, 2019) and fear conditioning (Poli et al, 2023). We interpret this increase in pupil diameter as a sign that mice were strongly engaged by the arrival of the threat in all conditions in a similar manner.…”
Section: Discussionmentioning
confidence: 99%
“…After the threat of the rubber paw, we observed pupil dilation that can also be observed when only the threat is applied without prior exposition to the prosthesis and tactile stimulations (Figure S1). Pupil dilation has been shown to correlate with different arousal states (Reimer et al, 2014; Turner et al, 2023), attention (Abdolrahmani et al, 2021), as well as the processing of startling stimuli (Leuchs et al, 2019) and fear conditioning (Poli et al, 2023). We interpret this increase in pupil diameter as a sign that mice were strongly engaged by the arrival of the threat in all conditions in a similar manner.…”
Section: Discussionmentioning
confidence: 99%
“…HAPLN1 is emerging as an important extracellular molecule implicated in memory, independent of our use as a target for genetically encoded labeling in the ECM. Disrupting PNNs in a HAPLN1 (Crtl1) mouse knock-out model rendered fear memories susceptible to erasure 44 . HAPLN1 turnover was found to be relatively rapid in PNNs and at synapses 45 , and viral-mediated HAPLN1 delivery into mouse cortex showed that HAPLN1 is both necessary for PNN maturation in mice and when overexpressed can accelerate PNN and memory engram formation 46 .…”
Section: Discussionmentioning
confidence: 99%
“…The crucial role of the cartilage link protein Crtl1 in making fear memories resistant to deletion has been shown in the experimental model of fear extinction in Crtl1-KO mice [118]. Crtl1 is upregulated during brain development and participates in PNN condensation [46,143].…”
Section: Pnn In Fear and Memorymentioning
confidence: 99%